A new Neotropical species of the genus Parochlus Enderlein, 1912 (Chironomidae: Podonominae) and new distribution in Argentina - Rodríguez, Mariana Soledad (2009)
Adults and immatures of Parochlus carolinae n. sp. are described and figured. The specimens were collected from a stream and a river in the pampasic hills system in the centre-northern part of the San Luis Province, Argentina. The adult male is distinct in having hairy eyes. The pupa differs from other known species of the genus by the structure of the thoracic horn and the arrangement of setae on the anal spurs. The distribution of the genus Parochlus Enderlein is widened from an austral Andean Parochlus proper zone to a subtropical zone with Brazilian fauna.